2020
DOI: 10.1177/0144598720978007
|View full text |Cite
|
Sign up to set email alerts
|

Origin and paleoenvironment of organic matter in the Wufeng–Longmaxi shales in the northeastern Sichuan basin

Abstract: The formation environment and preservation conditions of sedimentary organic matter (OM) play an important role in the accumulation of shale gas. In the present study, inorganic and organic geochemical data were analyzed to determine the origin and preservation environment of sedimentary OM in the Wc-1 well of the Wufeng–Longmaxi (WF–LMX) Formation in northeastern Chongqing, China. In a biomarkers analysis, the numerical characteristics of n-alkanes ( n-C17/ n-C31>4.0), tricyclic terpenes (C23TT/C30H>1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…In this study, the middle-upper interval of the WF formation (approximately 4-10 m thick) and the GYQ and lower part of the LMX formations (approximately 2-10 m thick) were analyzed to determine the characteristics of marine redox conditions during this period. According to previous research which performed, vitrine reflectance measurement and clay mineral analysis, the four sections experienced a similar thermal evolution history, and the maximum burial temperature was approximately 210-250 °C (Su et al, 2007: Nie et al, 2018Wang et al, 2021;Xi et al, 2021).…”
Section: Paleogeography and Lithostratigraphymentioning
confidence: 87%
See 4 more Smart Citations
“…In this study, the middle-upper interval of the WF formation (approximately 4-10 m thick) and the GYQ and lower part of the LMX formations (approximately 2-10 m thick) were analyzed to determine the characteristics of marine redox conditions during this period. According to previous research which performed, vitrine reflectance measurement and clay mineral analysis, the four sections experienced a similar thermal evolution history, and the maximum burial temperature was approximately 210-250 °C (Su et al, 2007: Nie et al, 2018Wang et al, 2021;Xi et al, 2021).…”
Section: Paleogeography and Lithostratigraphymentioning
confidence: 87%
“…Based on paleogeographic reconstruction, the four study areas were concluded to be deposited in different water depth environments. The Datianba section, X3 well, and Shaba section (Qianjiang County, Chongqing Municipality, 29 °20′32.72″N, 108 °51′20.93″E) are located on the flank of the submarine highland of the Xiang'e or the structural saddle connecting it with the Qianzhong uplift, belonging to the shallow sea area, Wc-1 well (located in Chengkou City, Chongqing Municipality, 31 °54′26.67″N, 108 °32′58.21″E; Wang et al, 2021) is situated near the Qinling Ocean, and the water depth gradually deepens in this section (Figure 1B; Liu et al, 2016;Xi et al, 2021).…”
Section: Paleogeography and Lithostratigraphymentioning
confidence: 99%
See 3 more Smart Citations